2000
DOI: 10.1177/02750740022064759
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptions for Public-Sector Information Management

Abstract: This article reviews, analyzes, and assesses prescriptions for public-sector management of information technology (IT). It draws on four sources of such prescriptions: (a) the best-practices literature, based primarily on expert opinion and focused on managerial processes; (b) the empirical IT research literature, based primarily on quantitative analyses of the IT function; (c) benchmarks (the attempt to develop objective measures of the success of IT in public-sector organizations); and (d) the problem/disast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The private sector economic context rivets the attention of top business organization levels on SISP. The literature consistently maintains that SISP is critical to achieving a strategic competitive advantage or profitability for an enterprise [Boar, 2001;Rocheleau, 2000;Bajjaly, 1999;Doherty, Marples, and Suhaimi, 1999;Estabrooks, 1995;Segars, Grover, and Teng, 1998;Bryson and Alston, 1996;Bryson 1995;Neiderman et al, 1991;Sethi, 1998, 1996]. Strategic competitive advantage requires maintaining market share, insuring customer satisfaction, managing continuous improvement of process and product quality, and maintaining legal compliance and ethical stature.…”
Section: The Sisp Constructmentioning
confidence: 99%
See 2 more Smart Citations
“…The private sector economic context rivets the attention of top business organization levels on SISP. The literature consistently maintains that SISP is critical to achieving a strategic competitive advantage or profitability for an enterprise [Boar, 2001;Rocheleau, 2000;Bajjaly, 1999;Doherty, Marples, and Suhaimi, 1999;Estabrooks, 1995;Segars, Grover, and Teng, 1998;Bryson and Alston, 1996;Bryson 1995;Neiderman et al, 1991;Sethi, 1998, 1996]. Strategic competitive advantage requires maintaining market share, insuring customer satisfaction, managing continuous improvement of process and product quality, and maintaining legal compliance and ethical stature.…”
Section: The Sisp Constructmentioning
confidence: 99%
“…Today, IT planning must be weighed as a part of the process of establishing strategic objectives by converting simple IT planning to SISP and all that the model implies. [Rocheleau, 2000;Balutis and Kiviat, 1997]. Consideration of the use of IT to achieve strategic goals and objectives is a fundamental part of the process of selecting the strategic objectives that contribute the most value to an organization.…”
Section: Sisp and Setting Organizational Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few explicitly recognise the fundamental difference between project success (the realisation of business benefits) and project management success (on-time on-budget to specification) (Baccarini 1999;de Wit 1985). The result is that the number of success stories (however defined) is reported to be almost twice the number of failures (Falconer et al 1999;Rocheleau 2000). A project success perspective suggests the opposite situation is more likely to be true (Clegg et al 1997;Standish 1999;Standish 2003;Willcocks et al 1994;Young 2006b) Project management success has been shown not to strongly relate to project success (Markus et al 1994;Markus et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Early discussions of recommended guidelines addressed topics such as the use of consultants by public managers (Bowen & Collett, 1978) and the merits of policy evaluation (Bozeman & Massey, 1982) while, more recently, topics have ranged from information (Rocheleau, 2000) and human resources management (Coggburn & Hayes, 2004) to benchmarking municipal service quality (Folz, 2004) and emergency management (Henstra, 2010). Local public finance topics such as procurement (Duncombe & Searcy, 2007), the use of e-government during the budget process (Justice et al, 2006), and the prevention of local fiscal crises (Coe, 2008) have been examined as well.…”
Section: Literature Reviewmentioning
confidence: 99%